Antibacterial activity of Decursin from Streptomyces sp. GMT-8; an endophyte in Zingiber officinale Rosc. - Thongchai Taechowisan, Srisakul Chanaphat, Wanwikar Ruensamran, and Waya S. Phutdhawong (Journal of Applied Pharmaceutical Science, 2013)
Strain GMT-8 was isolated from the root tissue of Zingiber officinale Rosc. and identified as Streptomyces sp. on the basis of morphology, chemotaxonomy and 16SrDNA sequencing. It was an antagonist of Gram positive bacteria; Staphylococcus aureus ATCC25932, Bacillus cereus ATCC7064 and Bacillus subtilis ATCC6633. The inhibitory effect of the crude extract from the strain GMT-8 was examined based on the paper disc diffusion method (5 mg per paper disc) with three replications. It has been shown to have inhibitory activity against Gram positive bacteria. The major active ingredient from the crude extract was purified by silica gel column chromatography, thin-layer chromatography and identified to be decursin by NMR and mass spectral data, respectively. Bioassay studies showed that decursin had antibacterial activities against Gram positive bacteria with the minimum inhibitory concentrations within the range of 32 to 256 µg/ml.
Keywords: Antibacterial activity, decursin, endophyte, Streptomyces sp.